Comparative Analysis of Mathematics Anxiety and Academic Achievement among Science Education Students - Iheanacho Chukwudi Ike; Darlington Chibueze Duru; Uzoma Alwell; David Onyinye Mba (Brillo Journal, 2025)
This study examines the comparative analysis of mathematics anxiety and academic achievement among second-year Science Education students at Alvan Ikoku Federal University of Education, Owerri. Three research questions and hypotheses were tested at a 0.05 significance level. Using a correlation and comparative research design, all 85 students were included via census sampling. Data were collected using the Mathematics Anxiety Rating Scale (MARS), adapted from Al Mutawah (2015), and the Basic Mathematics for Science Education Achievement Test (BMSEDAT). MARS had 20 items with a Cronbach’s alpha reliability of 0.70, while BMSEDAT consisted of 6 essay questions, with a reliability coefficient of 0.71. Pearson’s correlation and independent samples t-test were used for data analysis. Findings revealed a significant relationship between mathematics anxiety and achievement, specifically among Biology students, but not in Chemistry and Physics. It was recommended that teachers should adopt positive, supportive teaching methods that encourage students to develop a healthy attitude toward mathematics.